Air-processed, efficient CH3NH3PbI3−xClx perovskite solar cells with organic polymer PTB7 as a hole-transport layer. Issue 82 (5th September 2015) - Du, Yangyang; Cai, Hongkun; Ni, Jian; Li, Juan; Yu, Hailong; Sun, Xiaoxiang; Wu, Yuxiang; Wen, Hongbin; Zhang, Jianjun
<x xml:space="preserve">Abstract</x> Solution-processed perovskite solar cells (PSCs), which utilized organic poly PTB7 as a hole-transport layer, achieved a power conversion efficiency (PCE) as high as 13.29% when fabricated in ambient air.